Perbaikan Kualitas Produk Kain Denim Di PT. Dunia Sandang Setia Abadi IV Sebelum Pengiriman Barang Menggunakan Metode Fault Tree Analysis (FTA) - Andi Muhammad Hilal Alamsyah BS.P (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
The quality of a product is built by the company by paying attention to the needs and desires of customers because an industrial factory will not exist if the products made or ordered are not in accordance with consumer desires. This study aims to determine the causes of fabric defects, especially in one of the Alaska brands in April 2023 as many as 825 defect cases. This research uses the Fault Tree Analysis (FTA) method used to analyze the causes of production defects such as underfeed, double feed, and non-standard thickness. The results of the study were found several factors causing defects in less feed, double feed, and thickness not according to standards, namely raw materials, machinery, and human factors. The improvement strategies during the production process are. Strict supervision and control, periodic training, proper machine maintenance, and selection of quality raw materials are strategies implemented to minimize fabric defects. implement supporting infrastructure to reduce product growth rates.